A Study on Prevention of Truancy in a Government School of Delhi - Pradhan, Rajashree (THE PRIMARY TEACHER, 2008)
Regular class attendance is a prerequisite to maximise the school’s contribution towards students’ achievements. Truancy is a widespread phenomenon that needs attention of researchers and school education planners. A study was conducted on 6th and 7th grade students of a Government Senior Secondary school in Delhi to explore reasons for truancy and to develop remedial strategies. Out of 110 students, 12 students were found to be frequently truant. Qualitative research techniques like observation and semi-structured interview of students, teachers and parents were used. The information obtained was analysed for finding out the possible reasons and factors behind truancy. Different strategies were evolved and implemented for preventing truancy and motivating these students to attend classes regularly. Various motivational, environmental and disciplinary strategies deployed by the researcher were found to be useful in reduction of truancy among students. The experience of this action research can be utilised in other similar situations and comprehensive strategies for prevention of truancy can be developed for wider implementation in school education system.